Detection of coinfection with Primate Erythroparvovirus 1 and arboviruses (DENV, CHIKV and ZIKV) in individuals with acute febrile illness in the state of Rio Grande do Norte in 2016. - Vanessa Dos Santos Morais; Lídia Maria Reis Santana; João Felipe Bezerra; Flavia Emmanuelle Cruz; Themis Rocha de Souza; Roozbeh Tahmasebi; Rafael Augusto Alves Raposo; Roberta Marcatti; Erick Matheus Garcia Barbosa; Philip Michael Hefford; Renata Buccheri; Ester Cerdeira Sabino; et al. (Public Library of Science (PLoS), 2023)
Background Arthropod-borne viruses, known as arboviruses, pose substantial risks to global public health. Dengue (DENV), Chikungunya (CHIKV) and Zika (ZIKV) viruses stand out as significant concerns in Brazil and worldwide. Their overlapping clinical manifestations make accurate diagnosis a challenge, underscoring the need for reliable laboratory support. This study employs a comprehensive molecular diagnostic approach to track viral infections in individuals with acute febrile illness, a period marked by widespread outbreaks of DENV, CHIKV and ZIKV. Methods Between January and August 2016, we received a total of 713 serum samples obtained from individuals with acute febrile illness, previously tested for DENV, CHIKV or ZIKV, with initial negative results, from LACEN-NATAL. Of the total 713 samples, 667 were from females (354 of them pregnant) and 46 from males. Molecular diagnosis was conducted using the Multiplex RT-qPCR technique for simultaneous detection of DENV, CHIKV and ZIKV. Additionally, we performed differential diagnosis by RT-qPCR for other viruses of the Flavivirus, Alphavirus Enterovirus genera and qPCR for Primate Erythroparvovirus 1 (B19V) species, in accordance with Ministry of Health guidelines. Results Among the 713 cases, 78.2% tested positive for viral infections, including 48% with CHIKV viremia, 0.6% with DENV and 0.1% with ZIKV. Arboviral coinfections totaled 2.4%, including DENV-CHIKV (1.7%) and CHIKV-ZIKV (0.7%). Moreover, 8% exhibited B19V viremia. Simultaneous infections were identified in 17.5%, encompassing B19V-CHIKV (17.1%), B19V-DENV (0.1%), and B19V-ZIKV (0.3%) Triple infections were observed in 1.3% of cases with B19V-DENV-CHIKV (1%) and B19V-CHIKV-ZIKV (0.3%). Conclusion Molecular testing demonstrated high efficacy in diagnosing prevalent arboviruses and detecting multiple coinfections. This approach helps to elucidate etiologies for symptomatic cases, especially during arbovirus outbreaks, and aids comprehensive surveillance. Our findings underscore the importance of monitoring co-circulating pathogens, such as B19V, with implications for clinical management, particularly in pregnant individuals. This study enhances our understanding of arbovirus epidemiology and reinforces the critical role of molecular diagnosis in disease surveillance and control.